Beyond Frequency: English Conjunction Use and Language Proficiency in Rural Ugandan Secondary Schools - Lehema Nuwagaba; Sulaiman Muhammad Isa; John Kintu (Journal of Educational Research and Practice, 2026)
English language proficiency is central to learners' academic participation in multilingual education systems, particularly in rural public schools where exposure to English may be uneven. This study examined the relationship between the use of English conjunctions and language proficiency among lower-secondary learners in selected public secondary schools in Ruhinda County, Mitooma District, Uganda. Guided by Systemic Functional Linguistics, the study adopted a cross-sectional mixed-methods design involving 269 Senior Three students and 15 English language teachers. Data were collected through student questionnaires, semi-structured teacher interviews, and documentary review of students’ written work. Descriptive statistics, linear regression, thematic analysis, and content analysis were used to examine patterns of conjunction use and their association with language proficiency. The quantitative findings showed a strong positive association between reported frequency of conjunction use and learners’ reported language proficiency. However, qualitative and documentary evidence indicated that frequent use alone did not sufficiently represent proficiency. Many learners relied heavily on basic coordinating conjunctions such as “and”, “but”, and “or”, while subordinating and correlative conjunctions were used with less confidence and accuracy. The findings suggest that the use of conjunctions is a meaningful marker of English language development when interpreted alongside accuracy, functional appropriateness, and syntactic variety. The study contributes to equitable and culturally responsive grammar pedagogy by showing the need to move beyond mechanical sentence joining toward meaning-oriented instruction that supports coherent academic communication in rural multilingual classrooms.